Are the impacts of wind energy reversible? Critically reviewing the research literature, the governance challenges and presenting an agenda for social science. (September 2021) - Windemer, Rebecca; Cowell, Richard
Highlights: Provides first systematic review of impact (ir)reversibility issues for renewables. Shows irreversibility to be a value-and position-dependent issue, not binary yes/no. Consequently, claims that impacts are (ir)reversible are always selective and partial. Review reveals patchy research attention to (ir)reversibility and long-term effects. Provides a conceptual framework for investigating impact (ir)reversibility Abstract: The extent to which the impacts of renewable energy development might be reversible is an important dimension of debates about environmental acceptability, magnified in significance by the sector's rapid expansion and the inexorable ageing of facilities. However, despite frequent claims that the impacts of renewable energy are reversible, the complex realities of impact (ir)reversibility have attracted minimal systematic research. This paper addresses this gap with the first review of the research literature on impact (ir)reversibility, focused on onshore wind, and makes a number of contributions. Firstly, it shows that determining whether impacts are reversible or not inevitably entails selective, value-laden judgements about what matters and why. Secondly, a problem with much of the existing literature on (ir)reversibility issues is its abstract and hypothetical nature, detached from actual end-of-life decisions about renewable energy facilities, and their relationship with sites and landscapes. These insights are used to generate a conceptual framework for investigating impact (ir)reversibility – emphasising the benchmark, value basis, object of focus, allocation of responsibility, and regulatory mechanisms - and the ways that long-term, end-of-life impacts are governed. The value of this framework is demonstrated through three empirical vignettes from the UK, and used to generate an agenda for future research.